SOCIO-AFFECTIVE STRATEGIES IN ENHANCING STUDENTS’ SPEAKING MOTIVATION - lystiana nurhayat hakim (Universitas Putera Batam, 2019)
This study investigated the use of socio-affective strategies to enhance the students’ motivation in speaking. Therefore, the purposes of the study were to find out the teacher’s way of using socio-affective strategies to enhance students’ motivation in speaking and to describe students’ perception toward socio-affective strategies in enhancing their motivation in speaking. A case study was used as a research design of this study. The data were collected through classroom behaviour observation, interview, and questionnaire. Furthermore, the writer used data triangulation technique to make the research result more valid. The finding of this study showed that there are six ways in using socio-affective strategies in teaching speaking; reducing students’ anxiety, encouraging students in speaking, controlling students’ emotion, asking question, cooperating with others, and empathising with others. The data also indicated that students have positive perception on using socio-affective strategies to enhance their motivation in speaking.